Sheikh Muhammad Muhājirīn’s Methodological Approach in Hadith Interpretation: A Theoretical Analysis - Fahmi Sahlan (ELS Journal on Interdisciplinary Studies in Humanities, 2024)
This study focused on a methodological analysis of Shaikh Muhammad Muhājirīn ’Amsār Bekasi al-Dārī in interpreting hadith, taking into account the contemporary challenges faced by modern society, and aims to explore his unique approach that integrates social, historical, and cultural contexts in interpreting hadith. The data collection method was carried out through documentation of the Sheikh's works, focusing on his book Miṣbāḥ al-Ẓalām Sharḥ Bulūgh al-Marām min Adillah al-Aḥkām as a primary source. Data analysis was carried out based on a hermeneutic approach, living tradition, and contextual theology that lead to a more holistic understanding. The findings showed that Shaikh Muhammad Muhājirīn ’Amsār Bekasi al-Dārī not only considers the text, but also seeks to create a dialogue between Islamic teachings and modern issues, such as social injustice and environmental change. The conclusion of this study confirmed that the Sheikh's methodological approach opens up new insights in more applicable and responsive hadith studies. The contribution of this study lies in the introduction of the Sheikh methodology as a dynamic model, providing a new perspective in the academic world. The limitations of the study lie in the narrow geographical focus and the analysis that does not cover the entire historical track. Suggestions for further research include exploring the application of this approach in international contexts and various cultural backgrounds to produce a more comprehensive understanding of the teachings of the hadith.